2018
DOI: 10.1038/s41598-017-18651-w
|View full text |Cite
|
Sign up to set email alerts
|

Six domoic acid related compounds from the red alga, Chondria armata, and domoic acid biosynthesis by the diatom, Pseudo-nitzschia multiseries

Abstract: Domoic acid (DA, 1), a potent neurotoxin that causes amnesic shellfish poisoning, has been found in diatoms and red algae. While biosynthetic pathway towards DA from geranyl diphosphate and l-glutamate has been previously proposed, its late stage is still unclear. Here, six novel DA related compounds, 7′-methyl-isodomoic acid A (2) and B (3), N-geranyl-l-glutamic acid (4), 7′-hydroxymethyl-isodomoic acid A (5) and B (6), and N-geranyl-3(R)-hydroxy-l-glutamic acid (7), were isolated from the red alga, Chondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The early findings have been confirmed and it was demonstrated that the amino function in DA is generated by nucleophilic displacement of GPP by an unknown intermediate [23]. Recently, six compounds with potential functions in the condensation of GPP and l-glutamate were identified and their structure described [24]. The same study also confirmed N-geranyl-l-glutamic acid as a potential intermediate.…”
Section: Introductionmentioning
confidence: 76%
“…The early findings have been confirmed and it was demonstrated that the amino function in DA is generated by nucleophilic displacement of GPP by an unknown intermediate [23]. Recently, six compounds with potential functions in the condensation of GPP and l-glutamate were identified and their structure described [24]. The same study also confirmed N-geranyl-l-glutamic acid as a potential intermediate.…”
Section: Introductionmentioning
confidence: 76%
“…Domoic acid (DA, Figure 1 B) is a naturally occurring excitotoxin originally isolated from the marine red alga Chondria armata and produced by the diatoms Nitzschia , Pseudo-nitzschia and Amphora [ 33 , 34 ]. These toxic diatoms are found in polar, temperate, subtropical and tropical regions and are responsible for many toxic blooms worldwide affecting coastal environments in Europe, America or Oceania [ 35 ].…”
Section: Domoic Acidmentioning
confidence: 99%
“…S6). Recently, L -NGG was isolated in low abundance from the DA-containing red alga Chondria armata and shown through labeling experiments in P. multiseries to be a precursor to DA (24). These observations further implicate dabA as a gene that encodes a major step in DA biosynthesis.…”
mentioning
confidence: 99%
“…3A and figs. S7 and S8), of which 5a and 5b had been recently isolated from C. armata (24). DabC, however, showed minimal cyclization of other similarly N -prenylated glutamic acids (fig.…”
mentioning
confidence: 99%